Electrochemical performance of all solid-state fluoride-ion batteries based on thin-film electrolyte using alternative conductive additives and anodes - Anji Munnangi (Journal of Solid State Electrochemistry, 2018)
CaF2 and MgF2 were tested as active anode materials for solid-state fluoride-ion battery based on thin-film electrolyte. Tin oxide, indium tin oxide, and carbon nanotubes were applied as electronically conductive additives in the anode materials to increase the electronic conductivities. X-ray diffraction demonstrated that these conductive additives were stable during the processes of electrode preparation and charge/discharge. The electrochemical measurements indicated that the batteries using CaF2 as the active anode material and carbon nanotubes as the conductive additive possessed the best electrochemical performance. The 1st and 30th discharge capacities of 114 and 67 mAh g−1 were obtained at 160 °C when Bi metal was used as the active cathode material. Furthermore, possible reasons for voltage hysteresis and the capacity losses were studied.